2010
DOI: 10.1016/j.peptides.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gastric hormones by systemic rapamycin

Abstract: The mammalian target of rapamycin (mTOR), an evolutionarily conserved serine-threonine kinase, is an intracellular fuel sensor critical for cellular energy homeostasis. Gastrointestinal endocrine cells play a vital role in the regulation of energy balance by secreting hormones that inform the brain about energy supply. Here we showed the localization of mTOR signaling molecules in more than 90 % of gastric ghrelin cells and 36 ± 3% of gastrin cells, while no somatostatin-positive cell showed phospho-S6K1 immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Our studies suggest that gastric mammalian target of rapamycin (mTOR) activity is critical for the modulation of ghrelin production (Xu et al, 2009;Xu et al, 2010).…”
Section: Regulation Of Ghrelin Biosynthesismentioning
confidence: 92%
“…Our studies suggest that gastric mammalian target of rapamycin (mTOR) activity is critical for the modulation of ghrelin production (Xu et al, 2009;Xu et al, 2010).…”
Section: Regulation Of Ghrelin Biosynthesismentioning
confidence: 92%
“…No mTOR activity is detected in somatostatin positive cells. Furthermore, inhibition of gastric mTOR signaling by rapamycin demonstrates no effect on the synthesis and secretion of somatostatin [20] . All of this evidence supports that mTOR signaling selectively modulates the production of gastric hormones.…”
Section: Gastrinmentioning
confidence: 98%
“…A series of studies have identified mTOR as a potential candidate of fuel sensor in the gastric mucosa because of its expression in a distinct group of the gastric endocrine cells, its reciprocal relationship with energy status and its role in the regulation of gastric hormone production [1,5,20] .…”
Section: Gastric Mtor Is a Fuel Sensor Integrating Fuel Supply With Hmentioning
confidence: 99%
See 2 more Smart Citations